Constituents and Obstacles of Zero Based Budgeting in Libyan Municipalities: A Study on Municipalities in East Libya - Mohamed, Ahmad Ebrak Marajaa; Salama, Salama Saeed; Taher, Ahmad Lamin; Ejwida, Mohamed; Alrifady, Abdulkareen (Journal of Economic, Administrative and Legal Sciences, 2022)
The purpose of this study is to evaluate the constituents and obstacles of Zero-Based Budgeting (ZBB) in Libyan Municipalities. The study is based on an analytical descriptive approach, and the sample consists of (municipal council members, higher management, heads of departments, and personnel of the department of finance) in municipalities based in East Libya. Data was collected through distributing 60 questionnaires; out of which, 90% (54 questionnaires) were collected back. In order to test the hypotheses, the study employs One Sample T-testand One Way ANOVA test. The results of T-test reveal the existence of an adequate organizational structure and managerial environment at high level. However, sufficient human resources and effective accounting information system are partially available. The results also provide evidence of a number of obstacles of ZBB application. The results of ANOVA analysis suggest that there are no variances in the findings attributed to sample characteristics.